Dendrochronological study of Cedrus deodar Grown at Kumrat valley Dir Upper KPK, Pakistan: Evaluation of Tree Age and Increment Based on Increment Core - Sajad Sajad; Jawad Jawad; Ikram ul Haq (Jurnal Ilmu Pertanian Indonesia, 2021)
The present research was conducted for tree-rings study in a mixed stand of Himalayan Species Credur deodar in Kumrat valley Dir Upper KPK, Pakistan. Tree-rings analysis was related to the counting of tree ring. Random sampling method was used, and 70 sample trees were selected, tree heights and diameters were measured, and increment cores were collected from each sample-tree diameter at the height at breast point to be analyzed and studied in the laboratory. The objectives of the study were to determine the exact age of tree and to evaluate total and mean annual increment in the basal area and tree volume based on the increment cores. Regression models revealed the impacts of tree age on the basal area and tree-volume increment. Results showed the minimum basal-area increment was 0.0028 m2 at the age of 10 years, the maximum basal-area increment was 2.658 m2 at the age of 60 years, with mean was 0.95±0.677 m2 at the age of 36 years and R2 was 0.9593. The maximum tree-volume increment was 1.42 m3 at the age of 60 years, the minimum tree-volume increment was 0.010 m3 at the age of 10 years, with mean was 1.35±0.96 m3 at the age of 36 years and R2 was 0.9167. The minimum mean annual-basal area increment was 0.0027 m2, the maximum mean annual-basal area increment was 0.048 m2, and the average increment was 0.022±0.010 m2. The maximum mean-annual increment in tree volume was 0.068 m3 at the age of 60 years, the minimum mean-annual increment was 0.0039 m3 at the age of 10 years, with mean was 0.032±0.014 m3 at the age of 36 years and R2 was 0.8903. Results showed a strong positive relationship of tree age with area and volume increment. Keywords: Basal area, increment, tree age, volume